ACID LEACHING IN SKARN COPPER PORPHYRY SYSTEMS: THE TARUTINSK DEPOSIT, SOUTHERN URALS - Grabezhev A.I.; Murzin V.V.; Moloshag V.P.; Sotnikov V.I.; Belgorodskii E.A. (My University, 2004)
The Tarutinsk deposit as a product of a skarn copper porphyry system differs from proper copper skarn and copper-magnetite skarn deposits by development of acid-type alteration (sericitization) in granitoids. Secondary transformation and sulfidization of skarns were coeval with the formation of strong sericitization zones with vein-disseminated ore mineralization in granitoids. These zones are located below skarn orebodies and, together with skarns, compose structures (conduits) gently dipping to the massif center. The sericitization temperature was below 350degreesC (sericite of 2M(1) + 1M modifications). The vein-disseminated pyrite-chalcopyrite mineralization (Cu = 0.5-2.4 wt %, Au = 0.1-0.4 ppm, Mo = 20 ppm) in skarns and granitoids was formed at T = 170-295degreesC and P = 0.25-0.47 kbar. Magmatic fluid (delta(18)O = +4.7...+8.6parts per thousand) participated in the vein ore mineralization in skarn zones. Transformation of granitoids at some distance from skarn zones was related to fluid with a significant role of meteoric water (delta(18)O = -0.8...+7.7parts per thousand). Associated weak bulk sericitization was changed for propylitization with a decrease of S and Cu contents in the altered granitoids. Sulfur in pyrite has a juvenile isotopic composition (delta(34)S = -1...+3parts per thousand).